Be mine - James, Sabrina (New York : Point, 2009)
When she brags that she is entering the competition for the most romantic couple of the Valentine's Day Dance, Jennifer has only one problem--she needs a boyfriend.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Dating (Social customs) -- Fiction; Valentine's Day -- Fiction; High schools -- Fiction